Air pollution assessment using lichen biodiversity index (LBI) in Shah Alam, Selangor / Nurul Adibah Mokhtar - Mokhtar, Nurul Adibah (2020)
Biomonitoring technique was frequently used to monitor air pollution level. Lichens are the commonly used biomonitor since it has the ability to absorb toxic materials into their thallus system. A study was conducted in Shah Alam, Selangor to determine the species composition of lichen, to assess the air pollution status according to Lichen Biodiversity Index (LBI) and to quantify the effect of motor vehicle frequency on the LBI value and species composition of lichens. This study also aimed to identify the most tolerant and the most sensitive lichen species in the study area. A total of 21 sectionsin central Shah Alam were studied with 52 sampling stations were chosen based on the presence of Roystonea regia as the host tree for lichen. Frequency of lichen was collected using quadrat with a dimension of 10 x 50 cm2